Chef training in New Zealand : New Zealand catering trade training delivery from 1980 to 2000 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education (Adult Education) at Massey University, Wellington, New Zealand - Hudson, John Brittain (Massey University, 2003)
From 1980 onwards changes have occurred that have affected tertiary education and, across the board trade training in New Zealand. This study examines how change has affected the specific trade sector of catering and it's implication to training. 1980 saw catering training being delivered under an industry based apprenticeship system. The industry based apprenticeship was originally available in conjunction with selected polytechnics offering (British) London based City and Guilds Qualifications, as the recognized standard of training in New Zealand. In 2003 a range of providers is offering catering training very differently. Hospitality training is currently available through polytechnics, private training organizations, secondary schools and within the workplace. Two separate catering qualifications are also available in New Zealand; the research discusses possible implications this may have to catering trade training.
Keywords: New Zealand; Cooks -- Training of; Study and teaching; Food service; Cookery